Istidlal Batalnya Wudlu (Perspektif Imam Hanafi dan Imam Syafi’i) - Sutrisno Sutrisno (Program Studi Hukum Keluarga Islam, 2021)
This study aims to determine 1) How is Istidlal (the process of searching for and using arguments) to invalidate ablution according to Imam Hanafi and Imam Syafii and 2) What are the factors that cause the difference of opinion between Imam Hanafi and Imam Shafii regarding the cancellation of ablution. The research method used in this study is descriptive qualitative with a comparative approach that compares the opinions of two scholars about the cancellation of wudlu. The research results obtained are: 1) Istidlal: Imam Hanafi's istidlal regarding the cancellation of ablution was inspired by analogues and qiyas, because he was nicknamed